نمذجة نظام دارة تبريد امتصاصية لأغراض التكييف باستخدام برنامج EES. - ديب, ناظم (Latakia University Journal -Engineering Sciences Series, 2014)
تم في هذا البحث نمذجة نظام دارة تبريد امتصاصية يمكن استخدامها لأغراض التكييف باستخدام برنامج EES. كما تمت دراسة تأثير كل من درجة حرارة المولد والمبخر والمكثف على معامل أداء الدارة ومعامل التدوير وعلى عرض مجال التبخير في المولد ، وتحديد القيم والمجالات المثالية لكل جزء . تبين النتائج أنه كلما زادت درجة حرارة المكثف كلما انخفض معامل الأداء ، ومع ازدياد درجة حرارة التكثيف من الى فإن قيمة معامل التدوير تزداد ، بينما تنخفض كمية الحرارة المطروحة من المكثف إلى الوسط الخارجي عند نفس مجال درجة الحرارة السابقة . كما أن زيادة درجة حرارة التبخير يزيد من معامل الأداء . كما تم تطبيق هذه النمذجة على دارة تبريد امتصاصية تعمل على محلول (ماء + بروميد الليثيوم) حيث أظهرت النتائج أن زيادة درجة حرارة التبخير من الى تخفض قيمة معامل التدوير وتزداد كمية الحرارة المسحوبة من المكان المراد تبريده ( الانتاجية التبريدية ). In this research an absorptive cooling cycle system modeling which can be used for conditioning purposes by using EES program was done . By using this program , the effect of temperature of the vapor generator , the evaporator and the condenser on the performance of the vapor cycle and the circulating coefficient was studied as well as the effect of the evaporating range width in the generator and the definition the values and ideal ranges for each part . The result showed that whenever the condenser temperature increases the performance coefficient ( COP ) decreases , and by increasing the condensation temperature from 18 – 36 C , thus the values of the circulating coefficient increases , while the average temperature released from the condenser to the external environment decreases at the same range of the previous temperature , and that the increase of the evaporator temperature would increase the performance coefficient ( COP ) . An absorptive cooling circuit system modeling using water and lithium bromide was achieved . Results showed that the increase of the evaporator temperature of between 4 -13 C , the average of heat amount drawn from the desired place to be cooled would increase .